Einrichten und Zonieren : Spaces, Materials, Fit-out. - Kaiser, Marcus (Scale., 2014)
SCALE Furnishing | Zoning covers all the tasks of interior architecture and provides a valuable tool for designing everything from store fixtures to office spaces: connections for walls, ceilings, and floors are explained in detail.